Application of anisotropic thin plate theory for development of displacements for Silicon <111> crystals plates in cylindrical systems - Javidinejad, Amir (Zielona Góra: Uniwersytet Zielonogórski)
Silicon <111> crystal is one of the crystal orientations, which shows potential for application in micro device developments of pressure diaphragms for measurement purposes. To date, no theoretical basis has been examined to develop the deflections for computational analysis purposes [1]. This paper presents the development of the diaphragm deflections for Silicon <111> Crystal in Cylindrical coordinates system. The Silicon <111> crystal possesses transverse isotropic properties. Thus, an anisotropic thin plate theory is used here to develop the plate deflection. A numerical example is given to compare the theoretical results with Finite Element Analysis (FEA) results.
Keywords: transverse isotropic; thin plate elasticity; FEA; pressure diaphragm; anisotropic